Solarization with Recycled Polyethylene: A sustainable and innovative alternative for substrate disinfection in the commercial production of Tagetes erecta as an ornamental plant - Puerta, Analia Veronica; Rubio, Esteban Julian; Roca Quintela, Juan León; Karlanian, Monica (INTA y Sbera, 2026)
Poster